Effect of acute hypertension on sodium reabsorption by the proximal tubule - Koch, Karl M. (1968)
The effect of acute hypertension on sodium reabsorption by the proximal tubule was studied in rats by means of micropuncture methods. Hypertension was induced by bilateral carotid artery ligation and cervical vagotomy. Within a few minutes after blood pressure rose (30-60 mm Hg above control levels), a moderate natriuresis and diuresis began. Proximal sodium reabsorption, measured by two independent methods, was found to be markedly suppressed, both in absolute amount per unit length and per unit of tubular volume (C/πr(2)). The ratio between tubular volume and glomerular filtration rate (GFR) (πr(2)d/V(0)) was found to be increased. These observations indicate that the inhibition of proximal sodium reabsorption induced by hypertension cannot be explained by the tubular geometry hypothesis of sodium regulation. Several possible hormonal mechanisms were investigated. Intravenous d-aldosterone did not prevent the suppression of sodium transport due to acute hypertension, nor did chronic oral saline loading to reduce the renal content of renin. Constriction of the suprarenal aorta, with maintenance of a normal renal perfusion pressure, did prevent the inhibition of proximal transport during carotid artery occlusion, thus excluding an extrarenally produced natriuretic hormone as the mechanism. The observations are compatible with the view that sodium transport was inhibited either by an intrarenal natriuretic hormone or by an increase in the interstitial volume of the kidney produced by a transient hydrostatic pressure gradient across the peritubular capillaries. The latter seems more likely to us because of the rapidity of onset of the natriuresis, and because removing the renal capsule and releasing the surface interstitial fluid prevented the effect of hypertension on proximal sodium transport.